THE FUTURE OF ACCOUNTANCY: AUTOMATION AND THE ROLE OF ACCOUNTANTS IN THE AGE OF AI - Parizoda Ergasheva, (World Scientific Research Journal, 2025)
The accounting profession is undergoing one of its most significant transformations in decades, driven largely by the rapid advancement of automation technologies and artificial intelligence (AI). Traditional accounting tasks such as invoice processing, payroll management, auditing, and even financial forecasting, once highly dependent on human labor, are now being streamlined or fully automated by intelligent systems. These technologies offer unprecedented efficiency, cost savings, and accuracy, making them highly attractive to businesses worldwide.  However, this shift does not signal the end of the accounting profession; instead, it is re defining its future. The role of accountants is evolving from routine data handlers to strategic advisors who can interpret data, provide insight, and contribute to business planning. Modern accountants are expected to have not only financial expertise, but also digital literacy, critical thinking, and the ability to work alongside AI tools.